2018
DOI: 10.11606/s1518-8787.2018052000270
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study in a rural area

Abstract: OBJECTIVETo describe the planning, sampling, operational aspects of the field, and the sample obtained during a research conducted in a rural area, specifying and discussing the main logistical difficulties unique to these places and the solutions adopted.METHODSWe carried out a population-based, cross-sectional survey between January and June 2016, with a representative sample of the population aged 18 years or over living in the rural area of Pelotas (approximately 22,000 individuals), State of Rio Grande do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
10
0
6
Order By: Relevance
“…Because, unlike the urban area, it is characterized by a reality in which low income and low schooling level predominate, precariousness of homes and roads, as well as the lack of public transportation and, consequently, social isolation and difficulty in accessing social and health services, causing social and health inequalities to increase progessively. 3 Furthermore, based on a literature review regarding research studies that contemplate the health-disease-care process of the older adults living in rural areas, it was identified that these are still incipient, since few scientific publications were found. This gap allows for the justification of the development of new research with the purpose of understanding it in different social and cultural contexts and, therefore, of contributing to the planning, implementation, development, evaluation and (re)formulation of health policies, programs and actions with a view to providing culturally congruent care.…”
Section: Introductionmentioning
confidence: 99%
“…Because, unlike the urban area, it is characterized by a reality in which low income and low schooling level predominate, precariousness of homes and roads, as well as the lack of public transportation and, consequently, social isolation and difficulty in accessing social and health services, causing social and health inequalities to increase progessively. 3 Furthermore, based on a literature review regarding research studies that contemplate the health-disease-care process of the older adults living in rural areas, it was identified that these are still incipient, since few scientific publications were found. This gap allows for the justification of the development of new research with the purpose of understanding it in different social and cultural contexts and, therefore, of contributing to the planning, implementation, development, evaluation and (re)formulation of health policies, programs and actions with a view to providing culturally congruent care.…”
Section: Introductionmentioning
confidence: 99%
“…The study is part of a broader research project on the health of the rural population. 12 The municipality of Pelotas has a population of around 340,000 inhabitants. Approximately 7% of those individuals live in the rural area of the municipality.…”
Section: Methodsmentioning
confidence: 99%
“…9 We found few studies that assessed medication use in rural areas of Brazil. 10,11 Limitations of a logistical and financial nature hinder studies being conducted in rural areas, 12 where there is also less availability of health services and pharmacies close to people's homes. 13 These factors can interfere in the pattern of medication use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a descriptive-analytical cross-sectional study with a quantitative approach 15 , conducted in rural areas of a regional health department based in Alfenas, Minas Gerais, with 26 municipalities, whose PHC is primarily governed by the Family Health Strategy (FHS). According to the Brazilian Institute of Geography and Statistics (IBGE) 9 , the study's target population was 66,266 working-age rural dwellers, of which 28,837 women between 18 and 60 years and 37,429 men between 18 and 65 years.…”
Section: Methodsmentioning
confidence: 99%